Pengaruh Privasi, Keamanan, Keandalan, dan Transparansi Terhadap Minat Penggunaan Payment Fintech UMKM di Watukelir - Utami, Setiyawati Budi; Bawono, Andy Dwi Bayu; Sasongko, Noer (Widya Cipta - Jurnal Sekretari dan Manajemen, 2023)
The growth of fintech companies is driven by the swift progress of information technology. The change in people's lifestyles towards electronic financial systems is the main driving factor. In this context, it is important to continue to increase interest in using fintech by Micro, Small and Medium Enterprises (MSMEs). This study aims to investigate the effect of privacy, security, reliability, and transparency on interest in using fintech, both individually and collectively. The theory used is the Theory of Planned Behaviour, which involves the concepts of privacy, security, reliability, transparency, and usage intention. The research method used is descriptive quantitative. The research sample consisted of 150 respondents selected by purposive sampling method. The data were analyzed using multiple linear regression with the help of SPSS software. The results showed that privacy, security, reliability, and transparency positively and significantly affect the interest in using fintech by MSME players, both individually and collectively.